Implementation Of Aswaja-Based Character Education For SMK Nu Lekok Pasuruan Students - Chusnul Hamidiah; Agus Qowiduddin; Imamah Imamah (Universitas Maritim AMNI Semarang, 2024)
The implementation of character education in madrasah institutions has a strategic role in shaping the character of students, because these institutions not only aim to transfer knowledge, but also train students' soft skills through subjects related to Aswaja or NU at school. This study describes the implementation of Aswaja-based character education at SMK NU Lekok. This research is a type of descriptive qualitative research using the literature study method. The research was conducted on November 11, 2023 at SMK NU Lekok District, Pasuruan Regency, with the research subjects being 23 students of class XI Multimedia Department. Data collection was conducted through observation, interviews, and documentation. Data analysis used data reduction, data presentation, and conclusion drawing or data verification. The results of research related to the implementation of Aswaja-based character education in grade XI students at SMK NU Lekok show that the management of ASWAJA character education has been thoroughly integrated. In the implementation of ASWAJA character education at SMK NU Lekok Pasuruan, each teacher has full responsibility in providing character learning and being a role model. The implementation of ASWAJA character education in this school is designed to shape the character of students in accordance with the teachings of Ahlussunnah Wal Jama'ah, with the hope that they have good morals by developing and implementing as a form of routine every day.